![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(4x\left(x-1\right)-3\left(x^2-5\right)-x^2=x-3-\) \(\left(x+4\right)\)\(\)
<=> \(4x^2-4x-3x^2+15-x^2=x-3-x-4\)
<=> \(-4x+15=-7\)
<=> \(x=\frac{11}{2}\)
\(\left(2x^2-3x+1\right)\left(x^2-5\right)-\left(x^2-x\right)\left(2x^2-x-10\right)=5\)
<=> \(2x^4-10x^2-3x^3+15x+x^2-5-\left(2x^4-x^3-10x^2-2x^3+x^2+10x\right)=5\)
<=> \(2x^4-10x^2-3x^3+15x+x^2-5-2x^4+x^3+10x^2+2x^3-x^2-10x=5\)
<=> \(5x-5=5\)
<=> \(5x=10\)
<=> \(x=2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x ( 2x - 3 ) + 2 = 2x2 - 10
=> 2x2 - 3x + 2 = 2x2 - 10
=> -3x + 2 = -10
=> -3x = -12
=> x = 4
Vậy x = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(8x^3-x=0\)
\(\Leftrightarrow x\left(8x^2-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\8x^2-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm\sqrt{\frac{1}{8}}\end{cases}}\)
b) \(x\left(x-5\right)=2x-10\)
\(\Leftrightarrow x\left(x-5\right)=2\left(x-5\right)\)
\(\Leftrightarrow x\left(x-5\right)-2\left(x-5\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(x-5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\x-5=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=5\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Tìm x, biết:
1) 2x ( x - 5) - x ( 2x - 4 ) = 15
<=> 2x2 - 10x - 2x2 + 4x - 15 = 0
<=> -6x - 15 = 0
<=> -6x = 15
<=> x = -15/6
2) ( x +1)( x + 2 ) - ( x + 4 ) ( x + 3 ) = 6
<=> x2 + 2x + x + 2 - x2 - 3x - 4x - 12 - 6 = 0
<=> -4x = -16
<=> x = 4
3) 4x2 - 4x + 5 - x ( 4x - 3) = 1 - 2x
<=> 4x2 - 4x + 5 - 4x2 + 3x - 1 + 2x = 0
<=> x + 4 = 0
<=> x = -4
4) ( x + 3 ) ( 2x + 1 ) - 2x2 = 4x - 5
<=> 2x2 + x + 6x + 3 - 2x2 - 4x + 5 = 0
<=> 3x + 8 = 0
<=> 3x = -8
<=> x = -8/3
5) -4 ( 2x - 8 ) + ( 2x - 1 )( 4x + 3 ) = 0
<=> - 8x + 32 + 8x2 + 6x - 4x - 3 = 0
.......
6) -3 . (x-2) + 4 . (2x-6) - 7 . (x-9)= 5 . (3-2)
<=> -3x + 6 + 8x - 24 - 7x + 63 - 5 = 0
<=> -2x + 40 = 0
<=> -2x = -40
<=> x = 20
Còn lại tương tự ....
\(2x\left(x-5-x\right)=10\\ 2x.\left(-5\right)=10\\ 2x=-2\\ x=\dfrac{-2}{2}=-1\)